APPLICATION OF GUIDED INQUIRY LEARNING MODEL TO IMPROVE CRITICAL THINKING SKILLS OF THE STUDENT ON 11ST GRADE WITH DYNAMIC FLUID MATERIAL - TRIWINDA PENGUKIR, RANI; ADMOKO, SETYO (Inovasi Pendidikan Fisika, 2018)
This research aims to know the influence of guided inquiry learning process to improve critical thinking skills of the student on 11st grade with dynamic fluid material. Kind of this research that be used is quasi experimental with pre-test post-test group design where the researcher used one class of implementation and one class of replication. The population of this research is the student on 11st grade of Dharma Wanita High School. The sample of this research is XI-IPA 1 as the implementation class and XI-IPA 2 as the replication class. The variables in this research including manipulation variable is guided inquiry learning model, response variable is critical thinking skills, and control variable are fluid dynamic material, teacher, and learning time allocation. The technique of data analysis that used is normality-test and homogeneity-test as precondition-test, t-test, n-gain, and variant analysis. The result of this research shows that the learning process with applying guided inquiry learning model got a very good categories with the percentage of XI-IPA 1 class is 86,8% and percentage of XI-IPA 2 class is 85,7%. The result of t-test to know the significance results of pre-test and post-test that is 52,35 for XI-IPA 1 class and 51,17 for XI-IPA 2 class with ttable is 1,70, it shows H0 rejected so H1 accepted because of the tcalculate more large than ttable, so can be conclude that the results of pre-test and post-test is significance importance. The result of n-gain test to know the increasing of critical thinking skills of the student got the average is 0,72 for XI-IPA 1 class and the average is 0,71 for XI-IPA 2 class with the categories of this two class is high. The result of positive student?s response is the percentage between 84% until 92% for each a question, this results from both of class have a very good categories. This research can be concluded that guided inquiry learning process can be increasing the critical thinking skills of the student with the result of the increasing that significance and the positive student?s response that very good of the both class. Keywords: guided inquiry, critical thinking skills, and dynamic fluid.